MiR‐142‐3p regulates synaptopathy‐driven disease progression in multiple sclerosis. (6th October 2021) - De Vito, Francesca; Musella, Alessandra; Fresegna, Diego; Rizzo, Francesca Romana; Gentile, Antonietta; Stampanoni Bassi, Mario; Gilio, Luana; Buttari, Fabio; Procaccini, Claudio; Colamatteo, Alessandra; Bullitta, Silvia; Guadalupi, Livia; et al.
Abstract: Aim: We recently proposed miR‐142‐3p as a molecular player in inflammatory synaptopathy, a new pathogenic hallmark of multiple sclerosis (MS) and of its mouse model experimental autoimmune encephalomyelitis (EAE), that leads to neuronal loss independently of demyelination. MiR‐142‐3p seems to be unique among potential biomarker candidates in MS, since it is an inflammatory miRNA playing a dual role in the immune and central nervous systems. Here, we aimed to verify the impact of miR‐142‐3p circulating in the cerebrospinal fluid (CSF) of MS patients on clinical parameters, neuronal excitability and its potential interaction with disease modifying therapies (DMTs). Methods and Results: In a cohort of 151 MS patients, we found positive correlations between CSF miR‐142‐3p levels and clinical progression, IL‐1β signalling as well as synaptic excitability measured by transcranial magnetic stimulation. Furthermore, therapy response of patients with 'low miR‐142‐3p' to dimethyl fumarate (DMF), an established disease‐modifying treatment (DMT), was superior to that of patients with 'high miR‐142‐3p' levels. Accordingly, the EAE clinical course of heterozygous miR‐142 mice was ameliorated by peripheral DMF treatment with a greater impact relative to their wild type littermates. In addition, a central protective effect of this drug was observed following intracerebroventricular and ex vivo acute treatments of EAE wild type mice, showing a rescue of miR‐142‐3p‐dependent glutamatergic alterations. By means of electrophysiology, molecular and biochemical analysis, we suggest miR‐142‐3p as a molecular target of DMF. Conclusion: MiR‐142‐3p is a novel and potential negative prognostic CSF marker of MS and a promising tool for identifying personalised therapies. Abstract : By combining clinical and preclinical studies, De Vito et al. propose miR‐142‐3p to be a potential synaptotoxic and negative prognostic marker in multiple sclerosis. Keeping miR‐142‐3p at a low‐level through a personalised therapy may be a promising strategy to improve the disease course in multiple sclerosis.